A polyhedral oligomeric silsesquioxane functionalized copper trimesate1. Issue 40 (18th May 2015) - Sanil, E. S.; Cho, Kyung-Ho; Hong, Do-Young; Lee, Ji Sun; Lee, Su-Kyung; Ryu, Sam Gon; Lee, Hae Wan; Chang, Jong-San; Hwang, Young Kyu
<x xml:space="preserve">Abstract</x> A metal–organic framework (MOF), copper trimesate (Cu3(BTC)2), was selectively functionalized with aminopropylisooctyl polyhedral oligomeric silsesquioxane (O-POSS) to make the external surface of Cu3(BTC)2 hydrophobic and thereby enhance the stability of the material against humidity.